The Effect of Investor Sentiment, Investment Decision, and Profitability on Stock Returns Through Firm Value - Andini Nurwulandari; Maison Hamonangan (Politeknik Siber Cerdika Internasional, 2024)
Stock Return is the goal of investors in investing their capital and high company value is the company's goal. This study examines the effect of investor sentiment, investment decisions, and profitability on stock returns with firm value as an intervening variable. The population in this study were 25 public companies indexed on IDX SRI KEHATI in the period May 2018 - May 2023. The type of data is the company's annual panel in the form of volatility from stock price fluctuations. The data collection technique uses purposive sampling and the analysis method used is panel data regression with the Structural Equation Model (SEM) which is processed with STATA 16 software. The sample that meets the criteria is 14 issuers. The results showed empirical evidence (1) Investor sentiment has a negative and significant direct effect on firm value; (2) Investment decisions have a positive and insignificant direct effect on firm value; (3) Profitability has a positive and significant direct effect on firm value; (4) Investor sentiment has a negative and insignificant direct effect on stock returns; (5) Investment decisions have a positive but insignificant direct effect on stock returns; (6) Profitability has a negative and insignificant direct effect on stock returns; (7) Firm value has a negative and insignificant direct effect on stock returns; (8) Investor sentiment has a positive and insignificant indirect effect on stock returns through firm value; (9) Investment decisions have a negative and insignificant indirect effect on stock returns through firm value; (10) Profitability has a negative and insignificant indirect effect on stock returns through firm value. The Intervening test results with the Sobel test show that Firm Value cannot mediatthe Investor Sentiment, Investment Decision, and Profitability variables on Stock Returns.